Selfhood and the Soul Essays on Ancient Thought and Literature in Honour of Christopher Gill (Oxford Oxford University Press, 2017)
This is a collection of new and original essays arising from a conference held in 2013 to mark Christopher Gill's retirement from the chair of Ancient Thought at Exeter. All the essays in the volume contribute to a shared project-the exploration of ancient concepts of selfhood and the soul, understood in a broad sense-and, like the work of the honorand himself, these essays range widely across disciplinary boundaries between ancient philosophy, psychology, medical writing, and literary criticism. The thirteen contributions, which can be read separately or together, are marked by a diversity of approach and subject matter, as well as a commitment to examining central issues about the self, the experience of being a person, and the question of how best to live. The reader is taken on a journey through topics and themes including money, love, hope, pleasure, rage, free will, metempsychosis, Roman imperialism, cookery, and the underworld. In this way the volume aspires to its honorand's remarkable combination of range with focus. The international line-up of contributors includes many established figures in the fields of classical literature, philosophy, and ancient medicine, as well as several younger scholars.
English
Keywords: Ethics & moral philosophy; ancient philosophy, classical literature, selfhood, soul, ethics